Telaah kritis pemikiran J. Mark Halstead mengenai konsep pendidikan Islam dalam artikel “An Islamic Concept of Education” - Murniasih, Eri; Wahyuddin, Wawan; Muhajir (LPPM Universitas Ibn Khaldun, Bogor, 2024)
The concept of Islamic education continues to develop and is very interesting to study because many thoughts on Islamic education continue to emerge both from Muslim circles and from Western thinkers. This article aims to examine J. Mark Halstead's thoughts from his work entitled